Neurodevelopmental outcomes in very preterm infants: The role of severity of Bronchopulmonary Dysplasia. (January 2021) - Gallini, Francesca; Coppola, Maria; De Rose, Domenico Umberto; Maggio, Luca; Arena, Roberta; Romano, Valerio; Cota, Francesco; Ricci, Daniela; Romeo, Domenico Marco; Mercuri, Eugenio Maria; Vento, Giovanni
Abstract: Objective: Bronchopulmonary dysplasia is a chronic respiratory disease that still affects preterm neonates; its association with neurodevelopmental (ND) impairment is already known. Different studies investigated neurodevelopmental outcomes in infants with BPD, often using the old dichotomous definition (BPD vs Non-BPD). This retrospective study aims to evaluate the role of different BPD severity grades on ND outcomes at 24 months of corrected age (CA). Methods: All preterm infants born between 2011 and 2015 in the study hospital with a gestational age (GA) ≤ 30 weeks and discharged from our NICU were included and were divided in infants with and without BPD. Infants with BPD were divided into three severity groups as defined by NICHD/NHLBI Workshop in 2001, and were compared to their Non-BPD peers, matching them according to the same GA and year of birth. At 24 months postmenstrual age, we assessed general outcomes (growth and hospital readmissions) and neurodevelopmental outcomes (motor, developmental and sensory outcomes) with a standardized assessment. Results: We enrolled 89 patients affected by BPD of different grades of severity and a control group of 89 preterm infants without BPD. Infants with Moderate and Severe BPD showed a significantly higher corrected odds ratio (OR) for cognitive impairment compared to controls. Within the group of infants without severe disability (regarding Griffiths' scales), infants with Moderate and Severe BPD as well as infants with Mild BPD showed a significantly higher risk of a lower total Developmental Quotient (DQ) score, even after correction for confounding factors. Conclusions: Our study evidenced that not only Severe BPD infants, but also Moderate ones showed a higher risk of overall cognitive impairment at 24 months CA. Within the group of infants without severe disability, also those with Mild BPD had lower Griffiths DQ scores than those without. This would suggest that infants with BPD, regardless of severity, warrant neurodevelopmental follow-up. Highlights: Neurodevelopmental outcomes are often reported using old definition Non-BPD vs BPD. Most studies reported ND outcomes only at 18 or 22 months of corrected age. BPD severity is related to worse ND outcomes at 24 months compared to preterms without BPD. Moderate and Severe BPD infants had a higher risk of overall cognitive impairment. Mild and Moderate BPD infants had also lower Griffiths' scores compared to controls.